Deepa Thomas Nov 15th, 2012 9x-3y=12 --> eq.① 3x-5y=7 --> eq.② (x-3)(multiply eq.② by -3): -9x+15y= -21 --> eq.③9x-3y=12 -->eq.① -9x+15y=-21 --> eq.③ [9x-9x (cancel)]-3y+15y= 12-21 12y=-9 y= -3/4Replace y by (-3/4) in eq.①: 9x-3(-3/4)= 12 9x+9/4=12 9x=12-9/4 9x=39/4 x= 13/12x=-13/12 y=-3/4When x= 13/12 and y=-3/4 6(13/12) - 2(-3/4)= 8 ans D

## If 9x-3y=12 and 3x-5y=7 then 6x-2y =?A. -5B. 4C. 2D. 8

## Answer Question

Click here to Login / Register your free account

## Related Answered Questions

## Related Open Questions